The strain-rate effect of engineering materials and its unified model - YU Shui-sheng; LU Yu-bin; CAI Yong (Latin American Journal of Solids and Structures)
The test data of metals, brittle materials and polymers in high, medium and low strain-rate range were summarized. It was found that the dynamic strength or yield stress of these materials was not sensitive to strain-rate in the low and high strain-rate range (corresponding to weak sensitivity area and saturated zone). But in the medium strain-rate range (strong sensitivity area), the dynamic strength or yield stress of these materials was extremely sensitive to strain-rate. The strain-rate effect function in classic Johnson-Cook constitutive model could not describe these phenomena in the range of low to high strain-rate. Therefore, the strain-rate effect function in classic Johnson-Cook constitutive model has been modified to a strain-rate effect expression which is suitable for different materials. This new model can better describe the phenomena of the weak sensitivity area, strong sensitivity area and saturated zone. With this model, the fitted curves are in good agreement with the test data, and the parameters are different for different materials. Finally, the fitting parameters are given.